Critical Review of the Existence of Legal Fiction Principles in Indonesian Law - Nurhilmiyah (International Conference of ASEAN Prespective and Policy (ICAP), 2018)
The principle of Fictie Rechts or Legal Fiction is still embraced in Indonesian legislation. It does not matter that the principle is inconsistent with reality on the ground, which in fact creates more and more new problems. For example the application of laws in very remote areas. How can a rural person who has no access to information, if he does not comply with a rule that has been passed by the state through the state gazette, then without considering the absorption aspect of his information, he remains entangled in the law. Because he after the law was enacted, he was considered to know the law. This study uses normative legal research method by reviewing the literature related to legal fiction. Surely the principle that is deemed irrelevant to its real condition like this deserves no longer applied. For that required seriousness of government and society in participating eliminate this law fiction principle.The results of this research show that Indonesia still enacts law government and society as well, lawmaker or legislator and society publish that.